Preoperative evaluation in women with uterine leiomyosarcoma. A nationwide cohort study. (November 2016) - Skorstad, Mette; Kent, Andrew; Lieng, Marit
Abstract: Introduction: The goal of this study was to assess the sensitivity of different preoperative diagnostic tools used in women with uterine leiomyosarcomas. Material and methods: Retrospective cohort study of all women with verified uterine leiomyosarcoma in Norway in the period 2000 to 2012. Data were collected from the Cancer Registry of Norway and medical records. Results: There were 212 women diagnosed with uterine leiomyosarcoma in the 13‐year period. Histopathological examinations by fractional curettage or endometrial biopsies verified malignancy in 55/142 (38.7%). MRI suggested malignancy in 45/55 (81%) of the examinations. CT evaluations indicated suspected malignancy in 64/107 women (59.8%). Biomarkers had low sensitivity for leiomyosarcoma, but suggested more advanced stage disease when high values were detected. Stage IV disease was present in 53.1% versus 25.5% ( p  = 0.01) of women with CA 125 values above 35 kU/L, compared with women with normal CA 125 values. In 115/212 (54.2%), leiomyosarcoma was only diagnosed postoperatively by histopathological examination of the removed specimen. Conclusions: Preoperative diagnostic modalities appear to have low sensitivity for differentiating leiomyosarcoma from fibroids. In Norway, approximately 54% of uterine leiomyosarcoma are unidentified before surgery. MRI evaluation was the imaging modality with the greatest sensitivity in identifying leiomyosarcoma preoperatively.